2016
DOI: 10.1111/agec.12242
|View full text |Cite
|
Sign up to set email alerts
|

Price transmission, asymmetric adjustment and threshold effects in the cotton supply chain: a case study for Vidarbha, India

Abstract: This study examines price transmission asymmetries in Vidarbha's (India) cotton supply chain from 2002 to 2012. The analysis takes account of thresholds in price adjustments toward their long-run equilibrium. The first stage considers the price dynamics between international and Indian domestic cotton prices. The second stage considers price transmission from domestic to farm gate cotton prices in Vidarbha. Results from the first stage indicate that Indian and international cotton markets are well-integrated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Since the price is strongly related with cloth price, the policy should consider the influence to the whole value chain so that the cotton producers would gain benefit from value added [1]. Some scholars, however, suppose that information asymmetry exists in the price conduction on the cotton industry chain and puts farmers at a disadvantageous situation when selling raw cotton [2]. Some scholars have found that the value chain is disconnected by critically studying the obstacles in the value chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the price is strongly related with cloth price, the policy should consider the influence to the whole value chain so that the cotton producers would gain benefit from value added [1]. Some scholars, however, suppose that information asymmetry exists in the price conduction on the cotton industry chain and puts farmers at a disadvantageous situation when selling raw cotton [2]. Some scholars have found that the value chain is disconnected by critically studying the obstacles in the value chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adhikari and Putnam (2020); Dahl et al (2020) examine co-movement across the energy and agriculture commodities and document spillovers from oil to cotton prices. In the Indian context, Shrinivas and Gómez (2016) study price transmission across international prices (U.S.) and Indian domestic prices and find evidence of integration between Indian and international cotton markets. It can thus be observed that a lot of research has documented price transmission and volatility transfers from the U.S. to different economies including Canada, Australia, China, Brazil, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, a significant strain of the literature found APT, and several hypotheses have been explored by academics to explain such dynamics . Retailers’ market power is the most frequently identified cause (see, among others, Bailey & Brorsen, ; Borenstein, Cameron, & Gilbert, ; Lloyd, McCorriston, Morgan, & Rayner, ; McCorriston, Morgan, Rayner, & Rayner, ; Sckokai, Soregaroli, & Moro, ; Sexton, ; Shrinivas & Gómez, ; Simioni, Gonzales, Guillotreau, & Le Grel, ; Verreth et al., ), although further studies (Acosta & Valdés, ; Bettendorf & Verboven, ; Peltzman, ; Serra & Goodwin, ) conclude that the exertion of market power and high concentration ratios are not fully consistent with asymmetries. Consumers’ search costs may differ from one product to another, depending on the structure of the supply chain.…”
Section: Theoretical Frameworkmentioning
confidence: 99%